2015
DOI: 10.1523/jneurosci.4422-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Role of Astrocyte Calcium Signaling in Cortical Blood Flow Regulation

Abstract: Editor's Note: These short, critical reviews of recent papers in the Journal, written exclusively by graduate students or postdoctoral fellows, are intended to summarize the important findings of the paper and provide additional insight and commentary. For more information on the format and purpose of the Journal Club, please see http://www.jneurosci.org/misc/ifa_features.shtml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, a more recent study showed intact Ca 2+ responses in astrocyte processes in IP 3 R KO animals (Rungta et al, ; Srinivasan et al, ). In addition, other studies maintain that Ca 2+ in astrocyte processes and end‐feet plays a role in CBF regulation (Biesecker & Srienc, ; Dunn et al, ; Otsu et al, ), which our results tend to support. These conflicting results may have been conciliated by two recent studies showing how astrocytic Ca 2+ changes are essential for the dilation of capillaries, but not arterioles (Biesecker et al, ; Mishra et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, a more recent study showed intact Ca 2+ responses in astrocyte processes in IP 3 R KO animals (Rungta et al, ; Srinivasan et al, ). In addition, other studies maintain that Ca 2+ in astrocyte processes and end‐feet plays a role in CBF regulation (Biesecker & Srienc, ; Dunn et al, ; Otsu et al, ), which our results tend to support. These conflicting results may have been conciliated by two recent studies showing how astrocytic Ca 2+ changes are essential for the dilation of capillaries, but not arterioles (Biesecker et al, ; Mishra et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Petzold et al suggested that both pathways might converge upon increases in intracellular Ca 2+ , although through an unknown mechanism (Petzold and Murthy, 2011). Several different studies have examined the potential contributions of changes in astrocytic Ca 2+ to changes in arteriole diameter, and the results are somewhat varied (for discussions, see Biesecker and Srienc, 2015;Khakh and McCarthy, 2015;Munoz et al, 2015;Bazargani and Attwell, 2016;Lia et al, 2021). Takano and colleagues photouncaged Ca 2+ in astrocyte endfeet and found that this causes an increase in blood flow in vivo (Takano et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other roles have been suggested for astrocytes in NVC, such as extending the late vasoconstrictive phase of (Mulligan and MacVicar 2004, Metea and Newman 2006, Gordon, Choi et al 2008, Girouard, Bonev et al 2010) or amplifying the response (Gu, Chen et al 2018, Institoris, Vandal et al 2022). It has also been suggested that the astrocytic contribution to NVC is capillary-specific (Biesecker and Srienc 2015, Mishra, Reynolds et al 2016). Hence, we focused our investigation on the vascular inflow tract where a 1 st order capillary branch from the penetrating arteriole (PA).…”
Section: Introductionmentioning
confidence: 99%